Servant Leadership in Decentralized Waste Systems: A Mediation Model of Social Entrepreneurship and Flexible Work Practices - Nugraha Wijayanto; Nurul Asfiah; Ahmad Juanda (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
Servant leadership on employee work performance within a community-based waste management enterprise, emphasizing the mediating roles of social entrepreneurship and flexible working arrangements. The growing complexity of socio-environmental challenges, particularly in decentralized waste management systems, necessitates leadership approaches that not only enhance organizational performance but also foster community engagement and sustainability-oriented behaviors. Mechanisms through which servant leadership improves performance in grassroots social enterprises remains limited. Employee performance through the development of social entrepreneurial orientation and the implementation of flexible work practices. A quantitative research design was employed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Data were collected through structured questionnaires administered to 120 employees involved in a 3R (Reduce–Reuse–Recycle) waste management initiative and its affiliated community groups. The measurement model assessed reliability and validity, while the structural model evaluated direct and indirect relationships among variables. Servant leadership has a significant positive effect on social entrepreneurship and flexible working arrangements. Both variables act as mediators in enhancing employee performance, with social entrepreneurship demonstrating a stronger mediating effect. The total effect of servant leadership on performance is substantial, suggesting that leadership grounded in service values can stimulate innovative, community-oriented behavior while simultaneously enabling adaptive work structures. Flexible working arrangements contribute to improved efficiency and work-life balance, while social entrepreneurship strengthens proactive problem-solving and collective responsibility. Contributes literature integrating leadership theory with socio-technical and entrepreneurial perspectives in the context of community-based infrastructure systems. Social enterprises is not solely driven by managerial control but by the interplay of leadership values, innovation capacity, and work flexibility. Practically, Findings offer insights for policymakers and practitioners in designing leadership development and organizational strategies that support sustainable waste management and community empowerment. Future research is recommended to expand the model across multiple organizations to enhance generalizability and theoretical robustness.